2019
DOI: 10.21873/anticanres.13646
|View full text |Cite
|
Sign up to set email alerts
|

Oral Recombinant Methioninase, Combined With Oral Caffeine and Injected Cisplatinum, Overcome Cisplatinum-Resistance and Regresses Patient-derived Orthotopic Xenograft Model of Osteosarcoma

Abstract: Background/Aim: Osteosarcoma is a recalcitrant neoplasm which occurs predominantly in adolescents and young adults. Recently, using a patient-derived orthotopic xenograft (PDOX) model of malignant soft-tissue sarcoma (STS), we showed that oral recombinant methioninase (o-rMETase), in combination with caffeine, was more efficacious than o-rMETase alone in inhibiting STS tumor growth. In the present report, we determined the efficacy of o-rMETase combined with oral caffeine on a cisplatinum (CDDP)resistant osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…Our laboratory has recently developed oral rMETase (o-rMETase) which has been shown to be highly effective in mouse models of cancer as injectable o-rMETase (20)(21)(22)(23)(24)(25)(26)(27). In the present report, we show that o-rMETase prevents obesity in mice on a high-fat diet, thereby opening a new paradigm for obesity prevention.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Our laboratory has recently developed oral rMETase (o-rMETase) which has been shown to be highly effective in mouse models of cancer as injectable o-rMETase (20)(21)(22)(23)(24)(25)(26)(27). In the present report, we show that o-rMETase prevents obesity in mice on a high-fat diet, thereby opening a new paradigm for obesity prevention.…”
mentioning
confidence: 55%
“…Our laboratory developed rMETase from Pseudomonas putida, cloned in Escherichia coli, as a very efficient means of MR (16). A big advance was our laboratory's development of o-rMETase which makes administration safe and easy without side-effects (20,(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that PDOX models maintain the original histological and molecular characteristics after transplantation in mice (16,17). PDOX models provide osteosarcoma patients with specific and individualized treatment options (18)(19)(20). We previously showed that PIO could overcome doxorubicin resistance in the PDOX model of osteosarcoma (4).…”
Section: Discussionmentioning
confidence: 84%
“…These results suggest the use of a higher dose of methioninase and combination with chemotherapy to further control loco-regional recurrence. Our previous studies have indicated that the combination of chemotherapy with methionine restriction is often highly effective (18)(19)(20)(21)(22)(23)(24)(25)36).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that o-rMETase can be an effective treatment to inhibit recurrent tumor growth in TNBC, as a cancer-specific metabolism-targeted therapy. Our previous experiments have shown o-rMETase holds much promise (19)(20)(21)(22)(23)(24)(25)(36)(37)(38), as it is an oral drug, despite being a large tetrameric protein, with no known side effects. We recently published a study on the long-term treatment with o-rMETase of a patient with bone-metastatic prostate cancer (38).…”
Section: Discussionmentioning
confidence: 99%